Displacement, resettlement, and livelihood restoration: safeguard standards in practice. Issue 2 (17th February 2018) - Kabra, Asmita
ABSTRACT: This article presents a case study of development practice based on the author's experience of designing a livelihood restoration plan and monitoring its implementation. The plan was based on safeguard standards of a multilateral development bank that funded a private sector renewable energy project on land belonging to a vulnerable community in Central India. Illustrating the challenges faced in implementing and monitoring this plan and the reasons for its failure, the article argues that a complex set of institutional and individual relationships determine the way in which safeguard policies are translated into practice by diverse and interrelated actors.